Question
Asked Dec 17, 2019
4 views

Solve. (If there is no solution, enter NO SOLUTION.)

y2  =  2x
x − 2y  =  6
(x, y)  = 
 
 
 
 
 (smaller x-value)
(x, y)  = 
 
 
 
 
 (larger x-value)
check_circle

Expert Answer

Step 1

It is required to calculate the solution for the given set of equations:

help_outline

Image Transcriptionclose

у % 2х...... (1) х- 2у %36.....(2) = 6..

fullscreen
Step 2

Find the value of x from equation (1) and put it in the equation (2)

help_outline

Image Transcriptionclose

y = 2x=x =: .(4) 2 equation (2): +-3y-6=-y- – 2 y = 6 2 y - 4 y =12 y – 4y – 12 = 0 -6y +2y–12 =0 У(у-6)+2(у-6)-0 (y - 6)(y+2)=0 y = 6,-2

fullscreen
Step 3

Now put the value of y...

help_outline

Image Transcriptionclose

when y = 6 62 > x = 2 v? 36 = 18 when y = -2 -22 > x =-= 2

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra